Heterogeneidade individual e o processo de valoração dos estados de saúde - Kilvia Helane Cardoso Mesquita (2014)
Parameter estimates of valuation of health states are useful to trace how individuals in different societies perceive or assign values to different health states. To realize how the characteristics that determine individual heterogeneity influence the valuation of health states is relevant because such valuations may influence the results of cost-effectiveness and decisions on resource allocation. The main purpose of this study, therefore, is to understand how demographic, socioeconomic factors and health may influence the evaluation of health states. On the other hand, this work is a by-product of the first research in Brazil that uses the general population to estimate the parameters of health state evaluation through the descriptive system EQ-5D-3L. The option for this system was due to its qualities as a universal evaluation instrument; which allows broad international comparisons, fundamental to evaluate public policies. The research made use of a probabilistic sampling, stratified by sex and age, amounting to 3362 individuals, all Minas Gerais residents, which evaluated through the time trade-off (TTO) method 102 health states. Several econometric models were estimate to measure the influence of individual characteristic on health state evaluation. Statistical tests indicated that among all the models estimated the crossed random effects model was the more appropriate. Yet the main result from estimation is that the majority of the individual characteristics do not influence the way individual evaluate health states. The surprising part of this result is that in a state with such socio-economic disparities as Minas Gerais, differences of income and schooling do not affect health state evaluation. On the other hand, age, local residence, smoking habit, health experience and happiness perception do affect health state evaluation. Based on these results this work reinforces the necessity of estimating these parameters for each country. The reason for that is that even finding that socio-economic traits do not influence individual preferences for health states, culture, life experience and access to information do matter; that is, costumes are relevant for evaluation and must be taken into account in the design and adoption of new technologies for health.